Induction of IFN-beta and the innate antiviral response in myeloid cells occurs through an IPS-1-dependent signal that does not require IRF-3 and IRF-7. - Stephane Daffis (PLoS Pathogens, 2009)
Interferon regulatory factors (IRF)-3 and IRF-7 are master transcriptional factors that regulate type I IFN gene (IFN-alpha/beta) induction and innate immune defenses after virus infection. Prior studies in mice with single deletions of the IRF-3 or IRF-7 genes showed increased vulnerability to West Nile virus (WNV) infection. Whereas mice and cells lacking IRF-7 showed reduced IFN-alpha levels after WNV infection, those lacking IRF-3 or IRF-7 had relatively normal IFN-b production. Here, we generated IRF-3(-/-)x IRF-7(-/-) double knockout (DKO) mice, analyzed WNV pathogenesis, IFN responses, and signaling of innate defenses. Compared to wild type mice, the DKO mice exhibited a blunted but not abrogated systemic IFN response and sustained uncontrolled WNV replication leading to rapid mortality. Ex vivo analysis showed complete ablation of the IFN-alpha response in DKO fibroblasts, macrophages, dendritic cells, and cortical neurons and a substantial decrease of the IFN-beta response in DKO fibroblasts and cortical neurons. In contrast, the IFN-beta response was minimally diminished in DKO macrophages and dendritic cells. However, pharmacological inhibition of NF-kappaB and ATF-2/c-Jun, the two other known components of the IFN-beta enhanceosome, strongly reduced IFN-beta gene transcription in the DKO dendritic cells. Finally, a genetic deficiency of IPS-1, an adaptor involved in RIG-I- and MDA5-mediated antiviral signaling, completely abolished the IFN-beta response after WNV infection. Overall, our experiments suggest that, unlike fibroblasts and cortical neurons, IFN-beta gene regulation after WNV infection in myeloid cells is IPS-1-dependent but does not require full occupancy of the IFN-beta enhanceosome by canonical constituent transcriptional factors.